Employers' Perspective on Childcare Services for Hired Farm Workers. Issue 4 (2nd October 2017) - Lee, Barbara C.; Salzwedel, Marsha A.; Chyou, Po-Huang; Liebman, Amy K.
ABSTRACT: The goal of this project was to protect children while parents work in agriculture by improving off-farm services for children of migrant and seasonal farm workers. Large agricultural enterprises have policies forbidding children in the worksite. At the same time, their employees, who are trying to generate income, seek as many work hours as possible but often lack viable options for childcare services. As employers strive to increase their labor pool, and workers seek off-farm childcare, there is mutual interest in improving access to childcare services in agricultural regions dependent on large numbers of full-time and seasonal workers. This report describes the employers' perspectives on childcare needs of hired farm workers' families and their barriers and motivators to facilitating off-farm childcare services. Using descriptive survey research methodology, data were collected from a convenience sample of 102 agribusiness owners and Human Resource directors attending an agricultural conference regarding labor laws or personnel management. Results revealed significant differences for those companies employing more than 25 workers compared to their counterparts. Primary motivators for offering childcare as an employment benefit were improved employee morale, enhanced company reputation, and a more stable workforce. A major barrier was that half of large-scale enterprises lack guidance on how to provide childcare options for their workers. Survey results are being used to facilitate collaboration among employers, farm workers, and childcare providers to offer a safe, nurturing environment for children while their parents work in agriculture.